2018
DOI: 10.18596/jotcsa.351559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Chalcone Substituted Metallophthalocyanines: Electrochemistry, Spectroelectrochemistry and Catalytic Oxidation of 2-mercaptoethanol

Abstract: Novel metallophthalocyanines (M = Zn, Co) carrying four (E)-1-(furan-2-yl)-3-(4hydroxyphenyl)prop-2-en-1-one (chalcone) at the peripheral positions were sythesized. These complexes have been characterized by a combination of infrared spectroscopy (FT-IR), proton NMR (1 H-NMR), high resolution mass spectroscopy (HRMS), and ultraviolet visible (UV-Vis) spectrophotometry techniques. Also, cyclic voltammograms of these phthalocyanines were recorded and zinc phthalocyanine has one and cobalt phthalocyanine has two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…High stability of delocalized 18-electron π-conjugate system of phthalocyanine, especially upon formation metal complex, gives high stability to macrocycle, determines specific physical and physical-chemical properties of this compounds and causes a plurality of various usage [1][2][3][4][5][6][7][8][9]. Thus, the absorption in visible region based on π-π * transition allows to apply macrocycles as photoresistant dyes and pigments [10,11]. Metal ion complexes with opened d-electronic shell, for example Co(II), Fe(II), Mn(II), may act as catalysts in Merox-processes, while Mg(II), Si(IV), Zn(II), Cu(II), In(III), Ga(III) able to perform as photocatalysts, generating singlet oxygen [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…High stability of delocalized 18-electron π-conjugate system of phthalocyanine, especially upon formation metal complex, gives high stability to macrocycle, determines specific physical and physical-chemical properties of this compounds and causes a plurality of various usage [1][2][3][4][5][6][7][8][9]. Thus, the absorption in visible region based on π-π * transition allows to apply macrocycles as photoresistant dyes and pigments [10,11]. Metal ion complexes with opened d-electronic shell, for example Co(II), Fe(II), Mn(II), may act as catalysts in Merox-processes, while Mg(II), Si(IV), Zn(II), Cu(II), In(III), Ga(III) able to perform as photocatalysts, generating singlet oxygen [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Their skeleton structure and functional groups also make them well-known intermediates for the synthesis of various heterocyclic and bioactive compounds [23]. In literature showed that the introduction of chalcone groups into the peripheral/nonperipheral positions of phthalocyanines increased the electrochemical properties of phthalocyanines [24][25][26][27][28]. Also, phthalocyanines bearing chalcone groups have efficient photocatalytic, photophysical and photochemical properties [29,30].…”
Section: Introductionmentioning
confidence: 99%